TEACHER IDENTITY EXPERIENCED BY MR. BARTHES AS DEPICTED IN DETACHMENT MOVIE - Paulus Tri Nugroho Putro (English Language Education Study Program Association (ELESPA) or Asosiasi Program Studi Pendidikan Bahasa Inggris (APSPBI), Indonesia, 2018)
This paper investigates teacher identity which exists in the main character in a movie called Detachment. Mr. Henry Barthes (Adrien Brody) who is a substitute teacher and now he is teaching in a high school. While he is teaching, he has to encounter some distractions from Erica (Sami Gayle) a prostitute, one of his students, Meredith (Betty Kaye), and his colleague Ms. Madison (Christina Hendricks). While he faces the distractions, he has to deal with his childhood memory about the suicide of his mother and the death of his grandfather. All of distractions he faces at the end of the day he is able to handle the distractions and his teacher identity is a proof that his students adore him. The analysis data of the method is data analysis by watching the movie and the findings can be found in the movie in a form of how the teacher explains the material to the students, the teacher’s thoughts, and the teacher’s actions.